2002
DOI: 10.1002/sia.1471
|View full text |Cite
|
Sign up to set email alerts
|

Surface and electrochemical study of DBSA‐doped polypyrrole films grown on stainless steel

Abstract: Electrically conducting polypyrrole films doped with dodecylbenzenesulphonic acid (PPy-DBSA) have been electrochemically polymerized on stainless steel. The surface and electrochemical properties of the films were investigated by a combination of cyclic voltammetry (CV), scanning electron microscopy (SEM) and x-ray photoelectron spectroscopy (XPS). The CV results showed an irreversible reaction of electropolymerization. All PPy-DBSA films had a nodular or cauliflower-like surface morphology. The grain size was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…It can be seen that pure PPy film typically presents a ''cauliflower'' morphology. [10,11] The average diameter of the particles is about 1-2 mm. In Figure 1B, the conducting film prepared from 0.2 wt.-% pSA and 0.05 M pyrrole aqueous solution of pH ¼ 1.07 also had particles measuring about 1-2 mm, with some much smaller particles on the cauliflower surface, indicating that the main dopant is probably chloride ion.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that pure PPy film typically presents a ''cauliflower'' morphology. [10,11] The average diameter of the particles is about 1-2 mm. In Figure 1B, the conducting film prepared from 0.2 wt.-% pSA and 0.05 M pyrrole aqueous solution of pH ¼ 1.07 also had particles measuring about 1-2 mm, with some much smaller particles on the cauliflower surface, indicating that the main dopant is probably chloride ion.…”
Section: Resultsmentioning
confidence: 99%
“…The doping level may be calculated also using the [S total ]/[N total ] ratio and was found to be 42%. From the previous study 39 we found that excess DBSA on the DBSA-doped polypyrrole film was not removed by the rinsing process and was observed by SEM. The former calculation of doping level, therefore, is believed to be more accurate.…”
Section: Surface Study Of Polypyrrole Film Deposited On the Cu/ptfe Smentioning
confidence: 86%
“…23 These XPS data indicate that the surface composition of a DBSA-doped polypyrrole film deposited on Cu/PTFE is similar to those shown in our previous reports of DBSA-doped polypyrrole films grown on electropolished copper 32 and stainless steel. 39 The doping level-calculated from the ratio of total positively charged nitrogen to total nitrogen [ N 1C C N 2C /N total ]-of the polypyrrole/Cu/PTFE multilayer film was found to be 39%. The doping level may be calculated also using the [S total ]/[N total ] ratio and was found to be 42%.…”
Section: Surface Study Of Polypyrrole Film Deposited On the Cu/ptfe Smentioning
confidence: 99%
“…A two-electrode electrochemical cell was set up and the constant potential of 1.5 V was applied for 10 min at room temperature (28 C). According to the previous study, [11] the PPy film with the maximum doping level was achieved when the potential of 1.5 V was applied in the electropolymerization process. Black PPy film coated electrode was washed thoroughly with water to eliminate any loosely bound species.…”
Section: Experimental Partmentioning
confidence: 99%